1994
DOI: 10.1159/000097185
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization Stress May Increase Plasma lnterleukin-6 via Central and Peripheral Catecholamines

Abstract: It has recently been reported that both physical and psychological stress elevate plasma inter-leukin (IL)-6 levels independently of endotoxemia, tissue damage, or inflammation. However, the mechanism of plasma IL-6 elevation in these models is poorly understood. In the present study, plasma IL-6 levels were measured using the IL-6-dependent murine hybridoma subclone B9 cell line, which is commonly used by other investigators. We first demonstrated that an immobilization (IM) stress, a typical physicopsycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 0 publications
2
92
0
Order By: Relevance
“…Restraint stress caused transient elevation of serum IL-6 around 3 h (Fig. 1) as reported in the rat (Ando et al 1998;Takaki et al 1994). Nukina et al showed that the plasma IL-6 level peaked at 1 h after the onset of restraint stress in the mouse but they did not measure the value at 3 h (Nukina et al 2001).…”
Section: Discussionmentioning
confidence: 82%
“…Restraint stress caused transient elevation of serum IL-6 around 3 h (Fig. 1) as reported in the rat (Ando et al 1998;Takaki et al 1994). Nukina et al showed that the plasma IL-6 level peaked at 1 h after the onset of restraint stress in the mouse but they did not measure the value at 3 h (Nukina et al 2001).…”
Section: Discussionmentioning
confidence: 82%
“…After centrifugation, plasma samples were harvested and stored at Ϫ20°C. ACTH was determined in unextracted plasma by RIA by modifications of a method reported previously (Takaki et al, 1994), using [ 125 I]-human ACTH (ICN Pharmaceuticals, Costa Mesa, CA) and human ACTH antiserum provided by the National Hormone and Pituitary Program of the National Institute of Diabetes and Digestive and Kidney Diseases (lot AFP6328031). Synthetic human ACTH 1-39 (Sigma) was used as reference standard.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma corticosterone (CS) concentrations were measured by modifications of a method described previously (Takaki et al, 1994). Plasma samples diluted 1:100 in assay buffer (PBS containing 0.1% gelatin and 0.04% sodium azide, pH 7.4) were heat-denatured at 70°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…IL-6 levels have been reported by others to respond rapidly, rising within 15 min of exposure to psychological stress (11,68) and to return to baseline levels within 12-24 h after exposure to acute moderate stress, albeit in other models (48,71). TNF-␣ concentration is also known to be tightly regulated, rising within 30 min of exposure to stress, with an in vivo half-life of Ͻ2 h (16,18,38).…”
Section: Circulating Parametersmentioning
confidence: 99%